Entrepreneurial Challenges and Opportunities for Generation Z: A Qualitative Analysis - Susanto, Mashita Firdaus; Widiasih, Puti Archianti (Journal of Psychological Perspective, 2024)
Entrepreneurial activities are one of the important pillars of economic development efforts. the characteristics of Generation Z in Indonesia require a life balance between the work environment and their social or personal life. This research aims to find out the dynamics of entrepreneurial interest in Generation Z which will be reviewed in depth by researchers. The research method used is qualitative. The subjects of this research are entrepreneurs from Generation Z. The data were collected online using the online data collection technique. Data collection was conducted online using online data collection techniques. Data collection was conducted online using in-depth interview techniques. The data analysis process in this study went through four stages, data collection, data reduction, data display, and data verification. The results of this study show that the dynamics of entrepreneurship that occur in Generation Z are found in educational background, experience, desire to have an impact on others, self-confidence, utilization of technology, and support from the surrounding environment to develop an interest in entrepreneurship until finally deciding to carry out entrepreneurial activities. This research is expected to provide new knowledge about the dynamics of entrepreneurial interest in Generation Z and is expected to increase entrepreneurial interest in Generation Z today.